The development of swimming in Brazil and its structural intervening factors (El desarrollo de la natación en Brasil y sus factores estructurales intervinientes) - Mayara Torres Ordonhes; Camile Luciane da Silva; Vinicius Machado de Oliveira; Juliano de Souza; Fernando Renato Cavichiolli (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
This study aimed to identify how relationships are established in the development of swimming in a Brazilian sports entity, and hypothesized the existence of a structural dynamics sustained by hidden mechanisms of domination. The research consisted of a case study and the sample was a Brazilian sports entity in swimming, chosen from the analysis of the national classification in the period 2013-2018. Semi-structured interviews were conducted with two managers, two athletes and two coaches of the entity. The study had the following analytical categories: structured relationship between performance and participatory sports; coach influence on athlete development; financial support; sports facilities that provide good training conditions; club strategic planning; organization of a public policy framework for sport; political and sports structure; sports talent identification. After systematizing the data, these were analyzed together with Pierre Bourdieu's sociological theory. From the analyzed case, one can confirm the hypothesis that swimming has a relative social distinction in the Brazilian sports sphere, as links hidden mechanisms of domination in a structural way in its management, such as the different positions held in the specific subfield, the principle of capital differentiation, as well as the importance of raising public funds and the symbolic power of the entity.